TINGKAT KEPUASAN ORANG TUA ANAK TERHADAP PROGRAM UKGS INOVATIF IRENE’S DONUT - Ani Subekti; Hermien Rimbyastuti; Tri Wiyatini; Hermin Nugraheni (Jurnal Kesehatan Gigi, 2015)
TITLEParental and child satisfaction level to Irene’s donut innovative UKGS programABSTRACTUKSG innovative programs in kindergarten donut irene 's Al Azhar Banyumanik Semarang has been going on for 4 years. Has not been evaluated clinically and parent satisfaction. Program evaluation is very important to be a benchmark for the success of this program in order to continue. The purpose of the research was evaluated the implementation of innovative programs UKGS irene 's a donut in the review aspects of parental satisfaction in kindergarten Al Azhar Banyumanik Semarang.This research was a quantitative description of the cross-sectional approach. The subjects were 36 parents of students Al Azhar Banyumanik Semarang. The level of parent satisfaction was measured with a questionnaire instrument.The results showed the level of satisfaction of parents satisfied categorized as 100 %. Parents expressed satisfaction on the service aspect that is easy and fast , and his son felt comfortable dental examination. The financial aspects are still some parents who are not satisfied. It is advisable for the school and implementing UKGS to keep improving dental care and socialization of students financing system based parent agreement. Key words : innovative UKGS irene 's donut, the level of parent satisfaction___________________________________